2023
DOI: 10.1155/2023/6009414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Interaction between Abnormal Body Mass Index and Hypertension on the Risk of Type 2 Diabetes

Abstract: Objective. Many patients with type 2 diabetes have an abnormal body mass index (BMI) and hypertension together, but few studies on the interaction of the two on the risk of T2DM are reported. We aim to explore the effect of the interaction between abnormal BMI and hypertension on the risk of type 2 diabetes mellitus (T2DM) in Uyghur residents. Methods and Results. Based on the physical examination data of 27,4819 Uygur residents in Moyu County, a logistic regression model was used to analyze the correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
4
3
0
Order By: Relevance
“…The risk of T2DM in those with general/abdominal obesity was 1.65 and 1.69 times greater than in people without general/abdominal obesity, respectively after controlling for confounders. According to some studies [ 9 , 19 21 ] obesity is a risk factor for diabetes, which accords with our results. In people with general or abdominal obesity, the accumulation of body fat causes hyperinsulinemia and insulin resistance, which reduces glucose tolerance and the development of T2DM by impairing the use of glucose by muscle and other tissues [ 9 , 19 ], and obese people have a greater risk of acquiring diabetes than non-obese people do [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The risk of T2DM in those with general/abdominal obesity was 1.65 and 1.69 times greater than in people without general/abdominal obesity, respectively after controlling for confounders. According to some studies [ 9 , 19 21 ] obesity is a risk factor for diabetes, which accords with our results. In people with general or abdominal obesity, the accumulation of body fat causes hyperinsulinemia and insulin resistance, which reduces glucose tolerance and the development of T2DM by impairing the use of glucose by muscle and other tissues [ 9 , 19 ], and obese people have a greater risk of acquiring diabetes than non-obese people do [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to some studies [ 9 , 19 21 ] obesity is a risk factor for diabetes, which accords with our results. In people with general or abdominal obesity, the accumulation of body fat causes hyperinsulinemia and insulin resistance, which reduces glucose tolerance and the development of T2DM by impairing the use of glucose by muscle and other tissues [ 9 , 19 ], and obese people have a greater risk of acquiring diabetes than non-obese people do [ 9 ]. Losing weight is a crucial first step in lowering occurrence of T2DM, particularly in youthful people, as Studies have demonstrated that more than 80% of the physiological dysfunction of metabolic syndrome is caused by obesity [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations